The presidency of Barack Obama : a first historical assessment - Zelizer, Julian E., 1969- (Princeton University Press., 2018)
Barack Obama's election as the first African American president seemed to usher in a new era, and he took office in 2009 with great expectations. But by his second term, Republicans controlled Congress, and, after the 2016 presidential election, Obama's legacy and the health of the Democratic Party itself appeared in doubt. In the Presidency of Barack Obama, Julian Zelizer gathers leading American historians to put President Obama and his administration into political and historical context. Engaging and deeply informed, this is a must-read for anyone who wants to better understand Obama and the uncertain aftermath of his presidency.